Psychopathological comorbidities in medication‐overuse headache: a multicentre clinical study. (31st July 2015) - Sarchielli, P.; Corbelli, I.; Messina, P.; Cupini, L. M.; Bernardi, G.; Bono, G.; Di Piero, V.; Petolicchio, B.; Livrea, P.; Prudenzano, M. P.; Pini, L. A.; Sandrini, G.; et al.
Abstract : Background and purpose: In medication‐overuse headache (MOH) patients, the presence of psychopathological disturbances may be a predictor of relapse and poor response to treatment. This multicentre study aimed to assess the occurrence of psychopathological disorders in MOH patients by comparing the incidence of psychopathological disturbances with episodic migraine (EM) patients and healthy controls (HC). Methods: The psychopathological assessment of patients and HC involved the administrations of the Beck Depression Inventory, the Beck Anxiety Inventory, the Modified Mini International Neuropsychiatric Interview (M‐MINI), the Yale−Brown Obsessive Compulsive Scale (Y‐BOCS) and the Leeds Dependence Questionnaire. Results: The MOH, EM and HC groups (88, 129 and 102 subjects, respectively) differed significantly from each other for the presence of moderate/severe anxiety, whereas mood disorder and depression were revealed in similar proportions for both MOH and EM patients. By stratifying the M‐MINI questionnaire results according to the number of psychiatric disorders, it was found that MOH patients had a more complex profile of psychiatric comorbidity. Furthermore, clinically relevant obsessive−compulsive disturbances for abused drugs assessed by Y‐BOCS appeared to be more represented in the MOH group, whilst the prevalence of this trait in the EM group was comparable to that of HC (12.5%, 0.8% and 0%, respectively). Conclusions: Our study indicates the multiple presence of psychopathological comorbidities in patients with MOH. In light of this, it is recommended that the assessment of the psychopathological profile be included in an evaluation of MOH patients, allowing the clinician to more rapidly start an appropriate behavioural treatment, which would greatly improve MOH management.